A, The Psikologis Bagi Para Janda yang Ditinggal Mati: (Etika dan Efisiensinya di Lebakgedong Lebak-Banten) - Badrudin, Badrudin; Ainun Sifa, Isna (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
This research aims to find out the psychology of widows who have been left behind by their partners. The research object criteria were widowed women aged 27-40 years. Women who have been widowed for less than 5 years. The results of this research are that they still have not made peace with their past. They are still drowning in sadness. However, they also don't want to always be in this position. They want to experience change so they can make peace with their past and live a life without feeling pressure on their psychology. They have done well enough to make the change.